Central Role of Mast Cells in Mastocytosis, Hereditary α-Tryptasemia, Mast Cell Activation Syndrome, Urticaria, and Angioedema - Michael Rudenko (European Medical Journal Allergy & Immunology, 2022)
Mast cells are the central cells in the pathogenesis of many conditions that are associated with mediator release. New information is emerging about the role of mast cells in a number of conditions. This review summarises current knowledge on the topic. Some conditions such as mastocytosis have a confirmed genetic background; however, the genetic background of hereditary α-tryptasemia has only recently been described, and routine testing is yet to be set up in genetic laboratories. It is still unknown whether there is a genetic predisposition leading to the development of mast cell activation syndrome as well as urticaria and angioedema, and research is under way in this direction. The best known mediator contained in mast cells is histamine 2-(4-imidazolyl)-ethylamine, but it is not the only one. The effects of other mediators are significant in mast cell-mediated conditions, and can be future therapeutic targets. Diamine oxidase deficiency is responsible for digestive issues in some people, and although not directly linked with mast cell pathology, it falls under this umbrella due to symptoms related to the effects of externally consumed histamine. Mast cell-mediated diseases are usually defined through the detection of an elevation of mast cell mediators, response to antihistamines, mast cell stabilisers, and, in some cases, anti-IgE treatment when indicated. They comprise of mastocytosis, hereditary α-tryptasemia, mast cell activation syndrome, urticaria, and angioedema.